Many strides to freedom : African American women's unsung contributions and legacies - Carter-Robinson, Janelle Renee (African American women (Series), 2019)
"African American women have been integral to the various fights for equality throughout American history. Their importance to the movement occurred long before lifelong activist Rosa Parks became the catalyst in the Montgomery Bus Boycott in 1955. Who are the countless and often nameless black women who risked their lives and worked tirelessly to fight for the equality of black people in this country? From slavery to the modern day civil rights movement, the contributions of African American women are often overlooked in the retelling of history, but their contributions were critical in the battle for racial equality. They were grassroots organizers, strategists, and educators. Due to their selflessness and kindness, these black women became heroines of the movement. This book seeks to unearth the contributions of African American women throughout various periods of American history."--Publisher's description